1992
DOI: 10.1161/01.cir.86.5.1464
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency catheter ablation of left lateral accessory pathways via the coronary sinus.

Abstract: Radiofrequency catheter ablation of left lateral APs can be achieved effectively and relatively safely via the mid or distal coronary sinus when endocardial approaches are unsuccessful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(47 citation statements)
references
References 18 publications
0
44
0
3
Order By: Relevance
“…These results may be more expressive if a new study was carried out in the present, since the team now has a similar amount of experience with both approaches. As other authors reported [16][17][18] ablation of left free wall accessory pathway from the ventricular aspect of mitral annulus, failures occurred in 14 patients for an ideal local electrogram could not be recorded or accessory pathway could not be blocked permanently even with an ideal local electrogram. But, all of whom were successfully treated by ablation the atrial insertion site in a separate session-transseptal approach.…”
Section: Discussionmentioning
confidence: 92%
“…These results may be more expressive if a new study was carried out in the present, since the team now has a similar amount of experience with both approaches. As other authors reported [16][17][18] ablation of left free wall accessory pathway from the ventricular aspect of mitral annulus, failures occurred in 14 patients for an ideal local electrogram could not be recorded or accessory pathway could not be blocked permanently even with an ideal local electrogram. But, all of whom were successfully treated by ablation the atrial insertion site in a separate session-transseptal approach.…”
Section: Discussionmentioning
confidence: 92%
“…Not only chest pain 22) during the application, but also complications following RFCA in the coronary venous system, such as an occlusion 18) or thrombosis formation, have been reported. 22) The posteroseptal accessory pathway location included the area around and into the CS. CS angiography could be useful to understand the catheter position in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Of these 105 patients, 22 had an AP located in the posteroseptal region (PSAP group). The posteroseptal accessory pathway location was defined as the pathway located around the CS over the inferoposterior one-third of Koch's triangle, within 1 cm adjacent to the CS ostium over the inferomedial aspect of the right atrium or 2 cm to the left of the CS ostium at the crux area over the posterior medial mitral annulus.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Such pathways are frequently referred to as "epicardial" although it is clear that virtually all left lateral AP are epicardial and yet most are close enough to the LA endocardium that they are amenable to ablation from this site [34]. In these instances it may be useful to ablate via the coronary sinus when an excellent target EGM is attainable from the coronary sinus [35] these are infrequently seen with irrigated ablation catheters and reduced power, especially in the smaller more distal confines of the coronary sinus system. CS angiography can be useful prior to ablation in the region if proximity to coronary arteries is suspected, and to delineate the CS anatomy, especially a diverticulum [33,35].…”
Section: Coronary Sinus Ablationmentioning
confidence: 99%